O ensino superior nos governos petistas: uma análise temática dos discursos presidenciais de 2003 a 2016 - Diniz, Bruna Mello (Universidade Federal de São Carlos, 2022)
The trajectory of Brazilian higher education is marked by some characteristics that have given it unique contours. First, it is significant that while universities entered the scene in other Latin American countries at the beginning of Spanish colonization, in the mid-16th century, the first universities founded in terra brasilis date only from the beginning of the 20th century. This is because, among us, higher education followed the model of isolated schools, of French inspiration, for the purpose of professional training – a factor that certainly contributed to its late development, which began only after 1808. Secondly, another distinctive aspect is the emergence, accentuated after the military dictatorship, of a non-university higher education arrangement massively dominated by the private sector, while public universities until 1980 occupied a timid fraction within this system. Henceforth, intense political, economic and social processes shaped the new directions of higher education in the country, which, under the command of Fernando Henrique Cardoso, came to be dominated by private universities, which prospered in pursuit of privatist policies. From 2003, however, a turning point emerged with the policies aimed at expanding Federal Institutions of Higher Education inaugurated by the governments of Luís Inácio Lula da Silva (2003-2010) and Dilma Rousseff (2011-2016). Considering this scenario and starting from the premise that the aforementioned policies produced profound transformations in Brazilian higher education, this research proposed to investigate whether in the official narratives of the Federal Executive during the PT administration, concerns about higher education were expressed and/or had already proposals for this sector have been outlined. In this sense, the methodology used consisted in carrying out a thematic analysis, with the help of the NVivo software, of the presidential speeches enunciated by Lula and Dilma from 2003 to 2016, in order to identify the presence of the education theme and, more specifically, of the higher education. From this, 3136 speeches were downloaded through the website of the Library of the Presidency of the Republic, which were later cut to 1368 referring to the topic of education, this being the corpus considered for the analysis. The main results of the research, in turn, showed that: 1) “education” was among the five most prevalent themes in the presidents' speeches; 2) “higher education” received more prominence in President Lula’s speeches, while Dilma gave priority to “technical education”; 3) “university and social development” was a theme highlighted both in Lula’s and Dilma’s speeches, denoting that these spaces were elected as bulwarks of social inclusion of historically excluded and marginalized groups, with special attention to the poor, women and black people; 4) the democratization of access to higher education also proved to be an expressive element in the speeches, with the themes “quotas”, “reservation of university vacancies” and “ENEM” mentioned frequently, even in the period preceding to the implementation of such policies.
Higher education in PT governments: a thematic analysis of presidential speeches from 2003 to 2016
La educación superior en los gobiernos del PT: un análisis temático de los discursos presidenciales de 2003 a 2016
Keywords: Discursos presidenciais; Análise temática; Ensino superior; Governo Lula; Governo Dilma; Presidencial speeches; Thematic analysis; Higher education; Lula government; Dilma government; CIENCIAS HUMANAS::SOCIOLOGIA; CIENCIAS HUMANAS::SOCIOLOGIA::OUTRAS SOCIOLOGIAS ESPECIFICAS